형태요소와 확률 분석을 이용한 관모봉 권곡의 빙하기원설에 관한 소고 - 이현희; 성영배; 유병용 (한국지형학회, 2015)
This study tested a hypothesis on glacial origin of cirques on the Gwanmo Massif, using two indoor analytical methods. 1) The morphological characteristic of glacial valleys can be found through analysis of morphological descriptors and their correlations of this study area. A strong correlation between the length and width of the valleys’ development was found which is not found in areas processed by streams, floods, and mass movements. 2) The probability of ice coverage was calculated with a binary regression tree model with 4 topographic contexts to consider the possibility of glacier’s existence. A high probability was found at high altitudes over 2200m, especially in northern slopes with low annual solar radiation, in the wetern mountains which is stoss side of the north-west winter monsoon, and the east slopes of the mountains which have low slope and concave form with low curvature. However, the ELA (Equilibrium Line Altitude) of this area was 1900~2100m and the valleys were not long enough for cirque glacier to grow into extensive valley glacier.